Effect of posture change on the geometric features of the healthy carotid bifurcation - Aristokleous, Nicolas; Seimenis, Ioannis; Papaharilaou, Yannis (My University, 2009)
Segmented cross sectional MRI images were used to construct 3D virtual models of the carotid bifurcation in 5 healthy volunteers. Geometric features such as bifurcation angle, planarity angle, asymmetry angle tortuosity and curvature were calculated for the normal head posture and were compared to the equivalent values acquired with the head rotated clockwise by up to 80 degrees. The results obtained have shown that head rotation causes: 1) significant variations in bifurcation angle, planarity angle, asymmetry angle and internal carotid artery angle 2) tortuosity changes for the braches but not for the common carotid and 3) significant curvature changes for the common carotid artery (CCA) but not for the branches. The significant geometric changes observed in most subjects with head posture, may cause significant changes in hemodynamics and warrants future investigation of the hemodynamic parameters related to the development of atherosclerotic disease such as low oscillating wall shear stress and particle residence times.
Keywords: Diagnostic imaging; Geometry; Hemodynamics; Hydrodynamics